PENGARUH SIKAP, PENDIDIKAN, PELATIHAN, DAN MASA KERJA TERHADAP KINERJA KARYAWAN PADA PDAM TIRTANADI MEDAN - Zulkarnain Zulkarnain; Suryani Hardjo (Analitika: Jurnal Magister Psikologi UMA, 2010)
Human resources is one of important factor in supporting the activity and viability of the company. Human resource management requires attention to the human aspect of employees as a primary asset of the organization. Employees are the planners, implementers and the controlling organization who always plays an active role in realizing the goals of the organization, therefore, organizations need to optimally utilize all the energy, ability, skill, talent and knowledge possessed by their employees by giving awards to employees as a dignified human being.The aim of this research is to investigate the influence of attitude, education, training, and years of service to employee performance in North Sumatra Province Tirtanadi taps. Samples used in this study were 100 employees taps Tirtanadi GCMS analysis used to find the influence of attitudes, educational, training, and working lives of employee performance is multiple linear regression.The result showed that there are three significant variables are the variables X2, X3, X4 and the variables are not significant is only one variable X1. Three significant variables for each value of variable t> ttable or may be mentioned 2.689, 5.348, and 2.375> 1.984. Simultaneous test results obtained F value = 28.965> 2.37; that Ho was rejected or it can be concluded significant. Results of data analysis to get the coefficient of determination obtained R2 value 0.462.